Community-Based Health Movement: Social Innovation and Stunting Revolution in Supiori Regency - Rijal, Rijal (Baileo: Jurnal Sosial Humaniora, 2024)
This article investigates the role of community-based health movements as a form of social innovation in addressing stunting in Supiori Regency, Papua. The study aims to explore how integrated strategies combining government initiative and grassroots participation can effectively combat stunting, which is not merely a health issue but also deeply rooted in the region’s socio-economic and cultural context. Using a structured descriptive qualitative approach, the research involved field observations, interviews with key stakeholders, and policy analysis to understand the dynamics and outcomes of stunting interventions. The findings reveal that Supiori Regency has successfully implemented a hybrid model that combines top-down governmental directives with bottom-up community engagement. This approach, driven by strong leadership—particularly the active role of the Regent—has facilitated cross-sectoral coordination among health, education, and economic departments. It has also promoted community ownership and responsiveness, contributing significantly to stunting reduction. However, the study also uncovers that stunting persists even among families receiving social protection assistance, indicating the limitations of sectoral and welfare-based approaches when applied in isolation. The novelty of this study lies in its emphasis on stunting as a multidimensional challenge requiring systemic and inclusive solutions beyond the health sector. It contributes to the development of social and human sciences by providing a grounded model of collaborative governance, localized innovation, and integrated public health strategy. The study recommends adopting holistic, community-centered frameworks in policymaking, particularly in marginalized regions, to achieve sustainable health outcomes.